CD81 Is Required for Hepatitis C Virus Glycoprotein-Mediated Viral Infection - Zhang, Jie (American Society for Microbiology, 2004)
CD81 has been described as a putative receptor for hepatitis C virus (HCV); however, its role in HCV cell entry has not been characterized due to the lack of an efficient cell culture system. We have examined the role of CD81 in HCV glycoprotein-dependent entry by using a recently developed retroviral pseudotyping system. Human immunodeficiency virus (HIV) pseudotypes bearing HCV E1E2 glycoproteins show a restricted tropism for human liver cell lines. Although all of the permissive cell lines express CD81, CD81 expression alone is not sufficient to allow viral entry. CD81 is required for HIV-HCV pseudotype infection since (i) a monoclonal antibody specific for CD81 inhibited infection of susceptible target cells and (ii) silencing of CD81 expression in Huh-7.5 hepatoma cells by small interfering RNAs inhibited HIV-HCV pseudotype infection. Furthermore, expression of CD81 in human liver cells that were previously resistant to infection, HepG2 and HH29, conferred permissivity of HCV pseudotype infection. The characterization of chimeric CD9/CD81 molecules confirmed that the large extracellular loop of CD81 is a determinant for viral entry. These data suggest a functional role for CD81 as a coreceptor for HCV glycoprotein-dependent viral cell entry.